STUDY OF DISPARATE SECTORS IN FISHERIES - RAJE, S. G.; SINGH, V. V.; SHARMA, ARPITA (Journal of Indian Fisheries Association, 2015)
Fisheries employ a number of people and fisheries industry is truly an amalgamation of various disparate sectors. Fisheries play an important role in Indian economy and it provides employment to a number of people. For planning of integrated development of fisheries industry and resource management, a considerable amount of information is required. In this paper a study of the disparate sectors with regards to the nature of work, number of workers, sex-wise participation, earning type and earning in Indian Rupees in the year 1991-92, 1992-93, 1993-94 and 1999-2000 has been done in a selected fishing village. The geographical locale where the study has been done is Versova fishing village which is a major fish landing centre in Mumbai. The study has revealed that there are a number of disparate sectors in fisheries and in thsi fishing village on an average, a boat owner provided employment to 30.60 people in the year 1994 and to 19.25 people in 1999. Though this number has shown a decreasing trend with the advancement of years, it is however, seen that a number of people are employed in various disparate sectors in fisheries. It is necessary to highlight this and in any developmental planning, all these sectors should be given equal importance. Keywords :Disparate sectors, Fisheries, Employment